Indonesia : Agriculture Public Expenditure Review 2010 - World Bank (Washington, DC, 2013)
The agriculture sector has been and will continue to be important for poverty alleviation efforts in Indonesia. Indonesia was very successful in increasing agriculture productivity during the 1970s and up to the early 1990s, but productivity stagnated during most of the 1990s, partly as a result of declining public investments. Public spending on agriculture has increased significantly in the last decade, but a large share of that spending has been allocated to subsidizing private inputs. The impact of public spending on productivity can be positive, but that depends on the composition of spending. While public goods and services will have a positive impact on growth, subsidizing private inputs is unlikely to have much of an impact. Reforms to the existing subsidies systems can be combined with continued assistance to poor farmers, while the freed up resources could be used to provide improved public goods and services. A reallocation of spending should be combined with renewed efforts to improve the efficiency through which key services are provided, in particular in the areas of R&D, extension services and irrigation.